Bimbingan Orang Tua dalam Membentuk Kemandirian Belajar Anak Usia Dini Melalui Media Buku Halo Balita - Hayatul Mala; Nurus Sa’adah (Jurnal Bimbingan dan Konseling Indonesia, 2021)
This study aims to describe parental guidance in independent learning for early childhood through the medium of the Halo Balita book with the research method using a descriptive qualitative approach. The subjects of this study consisted of 7 early ages with an age range of 3-6 years and located in Jeruk Village, Gucialit District, Lumajang Regency. While the informants used in this study were parents of 7 early ages who used the Halo Balita book. Data collection techniques in this study were through interviews and observations four times within two weeks. While the data analysis technique in this study consisted of 4 stages, namely data collection, data reduction, data presentation, conclusion drawing and data verification. The results of data analysis from this study are in establishing learning independence for early childhood, parents make various efforts in order to achieve maximum results, one of which is by using the Halo Balita book. Efforts made include getting children to do positive things every day, giving questions and explanations using language that is easily understood by children, parents always accompanying, guiding and supervising children when children learn and practice the contents of the Halo Balita book. These efforts turned out to be fruitful, which can be proven by the fact that children who are still at an early age can learn to read word for word, can learn to be independent in carrying out their daily activities and can learn to maintain cleanliness by disposing of garbage in its place.